Nikah Siri in Indonesian Legal Thought: Analysis of Prohibition and Criminal Sanctions - Usammah Abdul Hamid; Chaliddin Chaliddin (Siyasah Wa Qanuniyah, 2025)
In modern legal thought, the relationship between Islam and politics is often debated, with some scholars arguing that Islam does not regulate politics, while others view it as a comprehensive religion that encompasses the formation of the state and its political apparatus, with supreme power originating from God. This study aims to analyze Abdul Wahhāb Khallāf’s perspective on Islamic politics and its application within Indonesia’s democratic system, employing a library research method and a descriptive-analytical qualitative approach, drawing on Khallāf’s main work, As-Siyāsah As-Syar’iyyah Fī Syu’ūn Ad-Dustūriyyah Wa Al-Khārijiyyah Wa Al-Māliyah. The findings show that Khallāf sees a symbiotic relationship between Islam and politics, with his leadership theory emphasizing justice, public participation, and the protection of individual rights, which aligns with the principles of democracy in Indonesia. Khallāf’s thinking also supports a balanced distribution of power among the executive, legislative, and judicial branches, in accordance with the principles of checks and balances in a democratic system. Thus, this study concludes that Abdul Wahhāb Khallāf’s ideas can provide significant contributions to strengthening Indonesia’s democratic system, provided they are applied with contextual interpretation and responsiveness to changing times.